Potential benefits of male diploidy and female triploidy for parasitoid wasps used as biological control agents: A case study in Nasonia - Kelley Leung (Biological Control)
Parasitoid wasps are haplodiploid insects, but polyploidy (diploid males, triploid females) occurs for many species. In biological control, polyploidy may have beneficial effects on desirable biological related traits. However, this is only possible in species for which polyploidy does not impair essential biological functions, as in for instance species with Complementary Sex Determination (CSD), where inbreeding drives sterile diploid male production and extinction risk. Notably, while CSD polyploidy is better studied, most biological agents are non-CSD species. This includes model Nasonia vitripennis, a blowfly parasitoid that can be purposefully made polyploid and then produces a high number of reproductive polyploid individuals. To test baseline non-CSD polyploid utility, an outbred polyploid N. vitripennis transformer knockdown line (tKDL) was established and assayed for relevant traits for considering polyploids as biological agents. Male diploidy and female triploidy increased head width, a body size proxy. Polyploidy increased unmated lifespan in diploid males, but decreased it in triploid females. In first matings, haploid and diploid males had equal fecundity, but sperm depletion assays revealed reduced diploid male fitness overall. Triploid females had a reduction in parasitization ability. This reduced male fecundity and female parasitization in tKDL suggest that polyploid Nasonia parasitoids have limited direct use in biological control, particularly in this outbred background. They are possibly more suitable for preparative applications, such as retaining alleles with sex-specific benefits.